Seismic Performance Evaluation of Special RC Frames with Gravity Steel Columns under the Base Level. (30th June 2020) - Zaherdannak, Amin; Shabani, Amirhosein; Erfani, Saeed
Abstract : In many multistory buildings, basement levels are used as parking spaces. However, dimensions of reinforced concrete columns at these levels cause them to be unideal parking spaces. An alternative is to replace the RC columns in middle frames with steel columns that are not a part of seismic force resisting system and only support vertical loads, therefore have smaller sections. Using simply supported steel columns under the base level is beneficial not only because they have smaller cross-sections which lead to increasing the parking space but also these steel columns are easier to be replaced after any possible damages and can be considered as convenient alternatives compared to ordinary RC columns in construction. In this research, seismic performance of structures implementing the suggested alternative is evaluated using nonlinear static and dynamic analyses and compared to that of regular counterparts. Results show that these structures pass the acceptability tests proposed by FEMA P695 methodology. Moreover, seismic performance factors of these two structural systems have been calculated and proposed.